Effects of risperidone on psychotic symptoms and cognitive functions in 22q11.2 deletion syndrome: Results from a clinical trial - Latrèche, Caren; Maeder, Johanna; Mancini, Valentina; Schneider, Maude; Eliez, Stephan (Frontiers in Psychiatry, 2022)
Background: Carriers of the 22q11.2 deletion syndrome (22q11DS) have an enhanced risk of developing psychotic disorders. Full-blown psychosis is typically diagnosed by late adolescence/adulthood. However, cognitive decline is already apparent as early as childhood. Recent findings in mice show that antipsychotic medication administered during adolescence has a long-lasting neuroprotective effect. These findings offer promising evidence for implementing preventive treatment in humans at risk for psychosis. Methods: We conducted a 12-week double-blind randomized controlled clinical trial with individuals with 22q11DS. Recruitment difficulties resulted in a final sample size of 13 participants (n = 6 treated with antipsychotics and n = 7 receiving placebo). We examined the response to treatment and assessed its short- and long-term effects on psychotic symptomatology using the Structured Interview for Psychosis-Risk Syndromes (SIPS) and cognitive measures. Results: First, two treated participants discontinued treatment after experiencing adverse events. Second, treated participants showed a short-term improvement in 33.3% of the SIPS items, mainly those targeting negative symptoms. Third, reliable improvements in at least one measure of working memory and attention were respectively found in 83.3% and 66.7% of treated participants. Conclusions: This is the first double-blind study to investigate the potential neuroprotective effect of antipsychotics in humans at risk for psychosis. Our preliminary results suggest that antipsychotic treatment may prevent long-term deterioration in clinical symptoms and cognitive skills. Yet, given the limited sample size, our findings need to be replicated in larger samples. To do so, future studies may rather adopt open-label or retrospective designs to ensure sufficient power.